Islamic Education Teachers’ Efforts in Mitigating the Hazards of Smoking at SMP Negeri 28 Mataoleo - Lidia, Lidia; Ridwan, Muhammad; Darmayanti, Darmayanti (Journal of English Language and Education, 2025)
Smoking habits can have negative impacts on health, especially for adolescents who are still growing. As an educational environment, schools have a crucial role in increasing students' awareness of the dangers of smoking. This study is to investigate the methods used by Islamic Religious Education instructors at SMP Negeri 28 Mataoleo , Bombana Regency, to discourage smoking. Descriptive qualitative research methodology is applied, and data is gathered by documentation, interviews, and observations. The results of the study demonstrate that PAI instructors actively participate in educating students using a methodology grounded in religious principles, thematic learning, and character building through extracurricular activities and positive habits. In addition, cooperation between schools and parents also contributes to increasing the effectiveness of smoking prevention programs. Consequently, it can be said that PAI teachers are important in raising awareness of the risks associated with smoking by using a religious perspective and ongoing moral development.